Happiness in Romanian cities on the road from post-communism transition to EU accession - Camilla Lenzi; Giovanni Perucca (REGION, 2016)
The literature on life satisfaction in transition countries, and in particular on Romania, demonstrated that life satisfaction significantly differs across rural communities and cities of different size. The question addressed in this paper is whether these imbalances are stable over time or, instead, they become manifest in the presence of strong divergences in the economic growth rates of different kinds of communities. Results point out that in the period of sharp economic growth led by large urban areas, as the one experienced by Romania on the road to EU accession, rural/urban disparities in life satisfaction widened, favoring cities of intermediate size.